HPW-Catalyzed environmentally benign approach to imidazo[1,2-a]pyridines - Martinho, Luan A.; Andrade, Carlos Kleber Z. (Beilstein Journal of Organic Chemistry, 2024)
The imidazo[1,2-a]pyridine moiety is present in drugs with several biological activities. The most direct way of obtaining this nucleus is the Groebke–Blackburn–Bienaymé three-component reaction (GBB-3CR) between aminopyridines, aldehydes, and isocyanides under both Lewis and Brønsted acid catalysis. However, several catalysts for this reaction have major drawbacks such as being expensive, extremely dangerous, strong oxidizing, and even explosive. In this scenario, heteropolyacids emerge as greener and safer alternatives due to their very strong Brønsted acidity. In particular, phosphotungstic acid (HPW) is an economical and green attractive catalyst for being cheap, non-toxic, and is known for its chemical and thermal stability. Herein, we report a straightforward approach to the GBB-3CR using HPW as catalyst in ethanol under microwave (μw) heating. This convenient environmentally benign methodology is broad in scope, provides the heterobicyclic products in high yields (up to 99%), with a low catalyst loading (2 mol %) in only 30 minutes, and allows the successful use of aliphatic aldehydes, substrates not so frequently explored with most usual catalysts for this reaction. Furthermore, the aforementioned advantages make this methodology very attractive and superior to the existing ones.
Keywords: GBB-3CR; imidazo[1,2-a]pyridine; microwave; phosphotungstic acid